THE ANALYSIS OF THE ROLE OF BUMDES AS AN EFFORTS TO EMPOWER VILLAGE COMMUNITIES - Widia Oktari; Desriadi; Ridan Aidil; Yogi Syahputra (Yayasan Wayan Marwan Pulungan, 2024)
This research aims to investigate the role of Village-Owned Enterprises (Bumdes) in empowering the community on Kedungung Island, using a qualitative approach. Kedundung Island, representing a rural area, possesses substantial natural resources potential, yet often faces developmental challenges and limited access to resources. The research employs a qualitative approach through in-depth interviews, participatory observation, and document analysis. Bumdes is the primary subject, while the rural community of Kedungung Island serves as the research object. The qualitative approach allows researchers to gain a deeper understanding of the dynamics of interaction between Bumdes and the local community. The findings reveal that Bumdes plays a significant role in enhancing the well-being of the rural community on Kedundung Island. Through the qualitative approach, this research illustrates various contextual aspects such as local cultural values, government policies, and socio-economic dynamics that influence the role of Bumdes in community empowerment. Bumdes on Kedungung Island has proven successful in managing various local economic potentials, including agriculture, fisheries, and tourism, taking into account the needs and aspirations of the community. Collective business development initiatives by Bumdes not only increase community income but also strengthen a sense of ownership and responsibility towards village development.